PEMBELAJARAN BERBASIS MASALAH UNTUK MENINGKATKAN HASIL BELAJAR DAN MOTIVASI BELAJAR PAI - nuraeni nuraeni (Asaatidzah, 2023)
ABSTRACT This study aims to investigate how problem based learning significant to improve student’ learning outcome and student’ motivation in studying PAI in Kelas VIII-A in SMP Negeri 15 Cirebon. As a qualitative-descriptive classroom actional research, this study did in two cycles with 26 students as participant and conducted in sequences that involves preparating, acting, observating, and reflecting. Data collection did by investigating students worksheet and recorded video, the finding then analyzed qualitatively according to the relevant theories. This study then found that the implementation of problem based learning significant to improve student’ learning outcome and the application of relevant teaching learning video improve student’ motivation in learning. However, implementing problem based learning by using vido as teaching media in secondary school needs teacher’capabilit in classroom management.  Thus, further study is still recommended for better findings.